Cultural Comparisons: A Comparison of Tea Drinking Traditions in Java and Sichuan - Rahmanita, Raisya; Basamah, Shofia Azra; Rudiansyah, Rudiansyah (Linguistik, Terjemahan, Sastra (LINGTERSA), 2024)
Tea is a type of drink that has been around since ancient times. In fact, in some regions, tea has become an integral part of culture and an inseparable part of people's social life, and also contains philosophical values. In each region, tea has its own characteristics. This is based on the variety and type of tea leaves themselves as well as the way they are served which are different in each region. The diversity of types of tea and forms of presentation certainly cannot be separated from differences in the environment where the tea leaves grow, as well as the origin of the tea in a particular region. These two factors refer to the practice of drinking tea and the different ways of serving tea in each region. China will immediately come to mind when you hear the word tea, because its tea culture is still strong today. On the one hand, Indonesia still adheres to its tea drinking culture. Tea has its own position in the traditions and practices of several cultures in China and Indonesia, especially in the Sichuan region and the island of Java. The aim of this research is to explore some of the differences that exist in tea drinking traditions in Java and Sichuan. We will also explore various cultural aspects that influence the practice of drinking tea, such as how tea is served, the type of tea used, related customs, and the symbolic meaning attached to the tea drinking ritual itself. So that in the end, readers will be able to appreciate the cultural diversity that exists in this world and encourage the exchange of knowledge and experience in tea drinking practices in both regions. The research method that is used is qualitative method of library research, namely collecting data by searching for sources and reconstructing information from various sources such as books, journals and existing research. The findings from this research are differences in the presentation and way of enjoying tea in Java and Sichuan.